The Use of Crypto Assets as Marriage Dowry Under The Compilation of Islamic Law and Indonesian Marriage Law - Bintang Ulya Kharisma (International Journal of Social Welfare and Family Law, 2026)
This Study analyzes the fulfillment of dowry requirements as mutamawwal property according to KHI Articles 30-38 and assesses the suitability of crypto assets as dowry under the positive law regime of the Marriage Law, including its implications for the protection of wives’ rights and legal certainty in the digital era. The research employs a qualititative method with a normative juridical approach through literature study of primary sources (the Qur’an, hadith, KHI, Law No. 1 of 1974, Bappebti and OJK regulations, an MUI fatwas) and secondary sources comparising journals, theses, and dissertations on crypto dowry and maqasid syariah, analyzed descriptively-analitycally and comparatively bertween Islamic law and positive law. The findings that demonstrate that normatively, crypto assets can be classified as valuable property within the KHI framework provided they meet the following criteria: possessing economic value, having clear specifications regarding type and amount, being transferable through legal mechanisms (such as gifts or wallet transfers), and being mutually agreed upon by boh parties. Consequently, they are valid as dowry with the value determined at the time of the marriage contract to minimize the impact or price volatility. However, it still poses potential value disputes, necessitating the strengthening of administrative guidelines at the KUA (office of Religious Affairs) and the enhancement of digital forensic capacty in Religious Courts. The study recommends further harmonization among the KHI, crypto asset regulations, and religious fatwas through the development of technical guidelines for crypto dowries oriented toward mashlahah and the protection of wives’ rights in the 4.0 era.